Los riesgos asociados al debilitamiento de la política comunitaria de cohesión - Flores, Gabriel (Papeles del Este, 2007)
The expansion of the EC to the east involves challenges that could end up negatively affecting the pace and depth of progress toward European unity. This appears even more true when the latest major expansion has coincided with a decrease in the relative weight of the Structural Funds, greatly weakening the communitarian policy of cohesion established to deal with the great economic, social and territorial inequalities these new Member States bring to the table. The article reflects on the causes, the forces and the factors that have caused the stagnation of the structural funds and on the relationship between the policy of cohesion and real convergence in the expanded EC.